Production and quality evaluation of a novel γ-aminobutyric acid-enriched yogurt - Zhu, Fei; Hu, Sheng; Mei, Lehe (Frontiers in Nutrition, 2024)
Objective: γ-aminobutyric acid (GABA) is a neurotransmitter inhibitor that has beneficial effects on various health conditions such as hypertension, cognitive dysfunction, and anxiety. In this study, we investigated a novel yogurt naturally enriched with GABA using a Levilactobacillus brevis strain isolated in our laboratory; the specific optimum yogurt production conditions for this strain were determined. Methods: We isolated an L. brevis strain and used it to produce yogurt naturally enriched with GABA. We explored the optimal conditions to enhance GABA yield, including fermentation temperature, inoculation amount, L-monosodium glutamate (L-MSG) concentration, fermentation time, and sucrose content. We also performed mixed fermentation with Streptococcus thermophilus and evaluated the quality of the yogurt. Results: Following optimization (43 °C, 8% inoculation amount, 1.5 g/L L-MSG, and 8% sucrose for 40 h of fermentation), the GABA yield of the yogurt increased by 2.2 times, reaching 75.3 mg/100 g. Mixed fermentation with S. thermophilus demonstrated favorable results, achieving a GABA yield akin to that found in some commercially available functional foods. Moreover, the viable microbe count in the GABA-enriched yogurt exceeded 1 × 108 cfu/mL, which is higher than that of commercial standards. The yogurt also exhibited a suitable water-holding capacity, viscosity, 3-week storage time, and favorable sensory test results. Conclusion: This study highlights the potential of naturally enriched GABA yogurt as a competitive commercial yogurt with beneficial health effects.